2021
DOI: 10.3390/s21124075
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Parent-Child fNIRS Hyperscanning Data Processing and Analysis

Abstract: The use of functional near-infrared spectroscopy (fNIRS) hyperscanning during naturalistic interactions in parent–child dyads has substantially advanced our understanding of the neurobiological underpinnings of human social interaction. However, despite the rise of developmental hyperscanning studies over the last years, analysis procedures have not yet been standardized and are often individually developed by each research team. This article offers a guide on parent–child fNIRS hyperscanning data analysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Motion-corrected time series were further visually inspected during a quality check procedure. We checked frequency-time plots of time-series for integrity, a clearly visible heart band, and visually observable motion artifacts ( Nguyen, Hoehl et al, 2021 ) resulting in the removal of 22.87% of channels of infants and caregivers. Then slow drifts and physiological noise were removed from the signals using a band-pass second-order Butterworth filter with cutoffs of 0.01 and 0.5 Hz and a slope of 12 dB per octave.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion-corrected time series were further visually inspected during a quality check procedure. We checked frequency-time plots of time-series for integrity, a clearly visible heart band, and visually observable motion artifacts ( Nguyen, Hoehl et al, 2021 ) resulting in the removal of 22.87% of channels of infants and caregivers. Then slow drifts and physiological noise were removed from the signals using a band-pass second-order Butterworth filter with cutoffs of 0.01 and 0.5 Hz and a slope of 12 dB per octave.…”
Section: Methodsmentioning
confidence: 99%
“…We will compare REC between observed neurophysiological coupling and random pairings of neural and physiological time series of participants to assess the degree of neurophysiological coupling. By establishing a baseline of coupling through surrogate analysis (e.g., Abney et al, 2015 ; Nguyen, Abney, et al, 2021 ; Nguyen, Hoehl, et al, 2021 ), we can compare properties of the observed PFC-RSA coupling against what might be expected by chance / spurious correlation. For the surrogate test, we will create surrogate data series combinations by randomly pairing the neural time series of each participant with the RSA time series of other participants.…”
Section: Methodsmentioning
confidence: 99%
“…Parent–child EEG and fNIRS are different hyperscanning approaches but supplement each other nicely (McDonald & Perdue, 2018). Parent–child fNIRS hyperscanning is an upcoming technique in the field of developmental neuroscience (for a practical implementation, see Nguyen, Hoehl, et al., 2021). fNIRS‐based brain‐to‐brain synchrony can be measured as aligned decreases and increases of hemodynamic processes in the same brain area at roughly the same time.…”
Section: Dual‐eeg: Defining the Conceptmentioning
confidence: 99%
“…In developmental research, hyperscanning comprises the simultaneous measurement of brain activity in parent/adult and child using different neuroimaging methods, including dual-EEG ( Atzaba-Poria et al, 2017 ; Leong et al, 2017 ; Krzeczkowski et al, 2020 ; Endevelt-Shapira et al, 2021 ; preprint Wass et al, 2018 ; Leong et al, 2019 ; Perone et al, 2020 ; Santamaria et al, 2020 ), dual-fNIRS ( Reindl et al, 2018 ; Azhari et al, 2019 ; Miller et al, 2019 ; Nguyen et al, 2020 , a , b , c ; Piazza et al, 2020 ; Quinones-Camacho et al, 2020 ; Wang et al, 2020 ) and dual-MEG ( Hirata et al, 2014 ; Hasegawa et al, 2016 ) or sequential-MEG ( Levy et al, 2017 , 2021 ). While all these studies clearly demonstrate that social interactions are marked by the coordination of two brains, so called brain-to-brain synchrony , the empirical methods used in these studies show great variability ( Czeszumski et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%